Part I : Characterization of LIN7B in iPSC- derived 3D cerebral organoids , Part II : Role of host proteins in late phase of influenza A virus infection - Bhat, Yashvi (IISER Mohali, 2023)
Full Pdf will be available soon
embargo period
Keywords: Biology